Mexican American women‘s perspectives of the intersection of race and gender in public high school: a critical race theory analysis - Fernandez-Bergersen, Sandra L. (Kansas State University, 2011)
This qualitative multiple participant case study examined Mexican American women‘s experiences at the intersection of race and gender in public high school. Mexican American women‘s experiences cannot be isolated and described independently in terms of either race or gender. The intersection of race and gender for Mexican American women has not been investigated fully. The few studies that include Mexican American females focus on dropouts and emphasize at risk factors such as gender, race, socioeconomic status, and language. Consequently, the gaps in the empirical literature are caused in part by the shortage of research on Mexican American women and the propensity toward examining Mexican American women from the deficit perspective. Critical Race Theory was the framework for the analysis and the interpretation in this study. The significant findings of this research support CRT, in that racism is prevalent and ordinary in the daily the lives of Mexican American females. The findings of the study included: First, racism is endemic and pervasive in public education. Second, colorblindness is the notion from which many educational entities operate. Third, the participants perceive social justice as the solution to ending all forms of racism and oppression. Finally, navigating the system is necessary to learn to be academically successful. The results contribute to the limited research on Mexican American women at the intersection of race and gender and the racism experienced in public high school to the overall CRT research in education, and in particular, to LatCrit research.
Keywords: Critical race theory; Mexican American women; Intersectionality; Inequities; High school; Storytelling; Education, General (0515); Ethnic Studies (0631); Women's Studies (0453)